The Teaching and Learning of Trigonometry in Tertiary Educations - Shubashini, Shubashini; Sokkalingam, Rajalingam (Cutin University Sarawak, Malaysia, 2011)
Trigonometry is an important part of mathematics at high school, college and university. Trigonometry is a subject that many university students find it difficult because it is not offered in depth in the high school to the extent that algebra and geometry were taught. The teaching professionals often said that the tertiary students’ knowledge about trigonometry was quite poor based on the assessments given to them. It has been observed that some of the elementary concepts of trigonometry are more easily comprehended than much of the usual work in algebra. The authors also believe that the teaching of trigonometry has to be developed from the meaning of the trigonometry functions as ratios (measurement of angles and sides of right angle triangles) and as number (compute the numerical value of the ratios representing different functions). Students should be acquainted with meanings of the tangents ration, the sine ratio, cosine ration and also terms as “angle of elevation” and “angle of depression”. Trigonometric functions appear to be difficult for the students due to the fact that their meanings have not been adequately explained. Therefore in this paper the authors want discuss further on how and what to be taught from trigonometric for the beginners in tertiary level.This paper suggests some of the avenues for exploration.